Peranan Penyuluh Pertanian dalam Pengembangan Kelompok Tani di Kelurahan Benua Nirae Kecamatan Abeli Kota Kendari - Lini, La; Hamzah, Awaluddin; Abdullah, Sukmawati (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
The purpose of this study was to assess the role of agricultural extension in the development of Farmers in Sub Benua Nirae, Abeli District of Kendari. This study uses a quantitative descriptively. Samples were used as research informants are 20 farmers who are members of 4 groups of farmers and also an Agricultural Extension Workers in Sub Benua Nirae, Abeli District of Kendari City. Agricultural Extension Workers in Sub Benua plays an important role in the development of farmer groups, especially as farmers supervisor, facilitator, organizer and motivator. The level of the role of educatorÂ judged by the farmers in good enough category